Eocene north–south trending dikes in central Tibet: New constraints on the timing of east–west extension with implications for early plateau uplift? - Wang, Qiang; Wyman, D.; Li, Zheng-Xiang; Sun, W.; Chung, S.; Vasconcelos, P.; Zhang, Q.; Dong, H.; Yu, Y.; Pearson, N.; Qiu, H.; Zhu, T.; et al. (Elsevier Science BV, 2010)
East–west extension has been a prominent feature of Cenozoic tectonics in central-southern Tibet, and the onset of this extension has been interpreted as indicating the surface uplift of the Tibetan Plateau to a critical level. Previous studies suggested that extension started in the Neogene between 18–13 Ma and 8 Ma, based on dating results from north–south trending normal faults, grabens or rifts, and dikes. We report here the discovery of widespread north–south trending diabase and andesitic porphyry dikes in and around the Shuang Hu graben, central Tibet, where crustal extension has previously been argued to start from 13.5 Ma based on mineral ages from graben-bounding faults. Our results show that dikes in this area were mainly formed in the Eocene (47–38 Ma). Geochemical and Nd–Sr isotopic data suggest that the diabase dikes originated from partial melting of an enriched lithospheric mantle source metasomatized by melts from subducted continental crust, and the andesitic porphyry dikes were probably derived from interactions between the subducted continental crust-derived melts and the mantle. Given that north–south trending Eocene dikes are found widely dispersed in central Tibet, we argue that the onset of east–west extension, and likely regional uplift of the Tibetan Plateau, began much earlier than previously thought. Our study implies that a large part of the Tibetan Plateau had already attained near-maximum elevation in the Eocene and is consistent with recent investigations regarding the Middle–Late Eocene (47–34 Ma) initiation of aridification in Asia, evidence from contemporary global oceanic O–Sr isotope curves and temperatures, and the carbon cycle.